Compatibility of Types III/IV Gypsum with Addition Silicone Impression Material - Elysia Santini; Octarina Octarina (Faculty of Dentistry, Universitas Trisakti, 2019)
Background: Addition silicone is an elastomeric impression material used to obtain an accurate impression. Compatibility between impression material and gypsum will affect the surface quality of the resulting models. Types III and IV gypsum are very commonly used in dentistry to pour impressions and produce working models; despite this, there has been no further research regarding the differences between the two types in terms of compatibility with addition silicone impression materials. Objectives: To compare the compatibility of types III and IV gypsum with addition silicone impression materials. Methods: Gypsum compatibility was assessed on the basis of its ability to reproduce lines of certain widths. Thirty samples were produced by impressing a stainless steel ruled block (in accordance with ANSI/ADA Specification No. 19) with addition silicone (independent variable) and then pouring in type III or IV gypsum (dependent variable). The samples were divided into two groups: in Group A, addition silicone was poured with type III gypsum; in Group B, addition silicone was poured with type IV gypsum. The lines from the stainless steel ruled block that formed in the gypsum samples were observed with a microscope at 10x magnification. Each line was then assessed with a score from 1 to 4, according to Morrow’s standardization, where a score of 1 indicates that the line was reproduced clearly and sharply over its entire 25 mm length, and a score of 4 indicates that the line is reproduced incompletely with roughness and/or blemishes. The data were analyzed using the Mann–Whitney U test. Results: Group B (addition silicone poured with type IV gypsum) produced more results rated as 1 (60% of the group’s samples) than Group A (only 46.67% of the group’s samples). Conclusion: On the basis of the number of scores rated as 1, type IV gypsum was more compatible than type III gypsum with addition silicone.